The impact of cigarette smoking on the quality of sleep in Polish men - Witek, Agnieszka; Lipowicz, Anna (Anthropological Review, 2021)
Quality of sleep directly impacts quality of life, whilst lifestyle significantly impacts night rest. Cigarette smoking is a serious threat to overall health, including sleep. Nicotine in cigarettes affects the nervous system, whilst the respiratory system is impacted by carcinogenic substances, such as dusts and tarred substances, inhaled with smoke. Cigarettes are assumed to be a risk factor in sleep disorders, including breathing sleep disorders. This study’s aim was to analyze the impact of cigarette smoking on adult men’s polysomnographic parameters. Polysomnographic records for 94 adult men were obtained from the polysomnography laboratory in Opolskie Province, Poland. Additionally co-morbidities, height, weight and frequency of smoking were also noted. Three groups of men were categorised according to the frequency with which they smoked: non-smokers, smoking less than a pack a day, smoking more than a pack a day. Compared to non-smokers and mild smokers, men who were heavy smokers also exhibited the longest sleepless time (H=8.11; p=0.017), the maximum waking time following the onset of sleep (H=7.99; p= 0.018), the lowest sleep efficiency across the three groups (H=7.96; p=0.019), the greatest number of apnea events per hour of sleep (H=6.23; p= 0.045), the lowest Oxygen Level Nadir (H=11.44; p= 0.003) and the highest rate of limb movements per hour of sleep (H=9.81; p=0.007). The dose effect was identified, which correlated more cigarettes men smoked per day with lower sleep quality.